(untitled) (NAU Journal of Library and Information Science, 2022)
The purpose of this paper was to examine the perception of information professionals on the availability and effective use of inspiring online library and information services during Covid-19 pandemic era in Anambra State. Four research questions guided the study. The research was focused on academic libraries. The research adopted a survey research design. Population of the study comprised information professionals from selected academic libraries in Anambra State, Nigeria. An online survey google questionnaire form was created to collect and analyze data from respondents. A total of 62 information professionals in the selected academic libraries responded to the online questionnaire form which was also used for the analysis. Data collected were analyzed using frequency count and percentages. Findings of the study revealed that inspiring online library information services should be embraced since the pandemic hindered physical visit to libraries. Poor Internet connectivity, paucity of funds, irregular power supply, ineffectiveness of Ask-A-Librarian services in most libraries, among others were some identified challenges militating against the availability and effective use of the inspiring online library information services. Based on the findings, recommendations were made on how to improve inspiring online library services in academic libraries in Anambra State.